The construction of family bonds in late adoption - Pordeus, Marcel Pereira (2021)
This study aims to discuss the construction of family affective bonds in late adoption. By methodology, we used the systematic literature review in scientific papers. As a result, we realize that it is significant that the adopter and adoptee want to build affective bonds. The loving bond between members of the same family is the key to answers and family harmony.